2014
DOI: 10.1063/1.4892654
|View full text |Cite
|
Sign up to set email alerts
|

A neutral oxygen-vacancy center in diamond: A plausible qubit candidate and its spintronic and electronic properties

Abstract: Spintronic and electronic properties of a neutral oxygen-vacancy (O-V) center, an isoelectronic defect similar to the negatively charged nitrogen-vacancy center in diamond, were studied by combining first-principles calculations and a mean-field theory for spin hyperfine interaction. It is elucidated that the neutral O-V center is stable in the p-type diamond and possesses an S = 1 triplet ground state and four spin-conserved excited states with the spin coherence times in an order of second at T = 0 K. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We first simulated the NV center and the OV center in diamond to validate our computational method. We confirmed that the defect C 3v symmetry and defect energy levels were in good agreement with the results reported by Gali et al 6) and Zhang et al, 26) respectively. We then studied the BV center in diamond.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…We first simulated the NV center and the OV center in diamond to validate our computational method. We confirmed that the defect C 3v symmetry and defect energy levels were in good agreement with the results reported by Gali et al 6) and Zhang et al, 26) respectively. We then studied the BV center in diamond.…”
Section: Introductionsupporting
confidence: 92%
“…22) The first criterion to be satisfied is the existence of a paramagnetic bound state that comprises at least two spin sublevels with finite energy splitting. The oxygen-vacancy (OV) center and the silicon-vacancy (SiV) center in diamond have been investigated for quantum bits 26) and single-photon interfaces, [27][28][29][30] respectively. On the other hand, boron-doped diamond, which is a p-type semiconductor, is widely used as a common electrode material in electrochemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a new family of NV --like defects possessing C 3v symmetry with a pair of substitutional impurity and adjacent vacancy and triplet (S = 1) ground states has been searched for by replacing the nitrogen atom with a firstrow element such as oxygen [32][33][34][35][36] and boron [32,37,38]. Figure 1(a) to 1(c) show schematic views of the one-electron state levels for the family of NV -, OV 0 , and BV -, respectively * Corresponding author: umeda.takahide.fm@u.tsukuba.ac.jp (see Appendix A for details).…”
Section: Introductionmentioning
confidence: 99%
“…In the OV 0 center, a 1 and a 1 are rewritten by 1a 1 and 2a 1 , respectively, and another a 1 state (denoted by 3a 1 ) is generated from an antibonding state of C-O bonds with three back-bonded carbon atoms [35]. Their energy positions are approximately shown in a band diagram [1,32,[35][36][37], where E C and E V are the conductionband top and the valence-band bottom, respectively.…”
Section: Introductionmentioning
confidence: 99%